Prehabilitation Oncologica Multimodal - Diana Molinares Mejia (Revista Colombiana de Medicina Física y Rehabilitación)
Physical function and quality of life are severely impacted by cancer and oncological treatments. In light of these findings over the last two decades, the focus of cancer rehabilitation research has shifted to preventive interventions. These interventions, known as prehabilitation, aim to improve patients’ physical, mental, and nutritional status before oncological treatment. The term prehabilitation was first defined in 2013 by Silver et al. as “a process on the cancer continuum of care that occurs between the time of cancer diagnosis and the beginning of acute treatment and includes physical and psychological assessments that establish a baseline functional level, identify impairments, and provide interventions that promote physical and psychological health to reduce the incidence and/or severity of future impairments. Since then, the impact of prehabilitation has been evaluated in multiple cancer types with beneficial results. This review aims to describe the benefits of rehabilitation in the cancer continuum and the effects on the different disease groups.